Testicular and epididymal parameters of spondias mombin L. (anacardiaceae) protected male wistar rats exposed to sodium arsenite (2014)
The testicular and epididymal protective potential of Spondias mombin. L in arsenic-treated rats was carried out. Thirty-five male albino rats (225-228g) were used and grouped into 7 (A to G), each group containing 5 rats. Group A was treated with 0.1ml Dimethysulphoxide (DMSO), B (0.1ml of Distilled water), C (Sodium arsenite; SA-2.5mg/kg body weight), D (Ethylacetate fraction), E (Ethylacetate fraction for 7 days and Sodium arsenite the 7th day), F (Methanolic fraction for 7days and Sodium arsenite the 7th day) and G (Methanolic fraction for 7 days). The results showed significant decrease (P>0.05) in the mean value of both the right and left testes length for group C (treated with Sodium arsenite only) compared to the remaining groups. It was also observed that Group G (treated with Methanolic fraction) had the lowest mean value (P>0.05) for the left and right testes weight and the left and right testicular diameter when compared to other groups. It was also observed that Group G (treated with Methanolic fraction) had the lowest mean values for all the epididymal parameters in this study. There was a significant decrease in the mean value of left epididymal weight, right and left epididymal length of group G compared to group B (treated with distilled water) and group A (treated with DMSO). It was concluded that the Methanolic fraction of Spondias mombin. L has no protective effect on the male albino rats exposed to sodium arsenite as it caused a reduction in epididymal parameters and testicular weight and diameter which may trigger testicular degeneration leading to infertility.